Highly efficient CuO/Cu@PC composite membranes for the photocatalytic degradation and sorption of roxithromycin from aqueous solutions - Dinara T. Nurpeisova; Anastassiya A. Mashentseva; Fatima Abuova; Saida H. Aleskhanova; Murat Barsbay (Results in Materials)
This study presents an effective approach to synthesis, characterization, and application of composite polycarbonate (PC) track-etched membranes (TeMs) embedded with copper (Cu) and copper(II) oxide (CuO) microtubes (CuO/Cu@PC) for the efficient removal of the antibiotic roxithromycin (ROX) from aqueous solutions. Using an environmentally friendly glyoxylic acid-based deposition method, Cu microtubes were deposited onto the PC TeMs and subsequently thermally annealed to generate a catalytically active CuO phase. Comprehensive structural analyses (SEM, SEM-EDX, XRD, XPS, AFM) confirmed the successful transformation of Cu into CuO, enhancing the material's photocatalytic and sorptive performance. Under UV irradiation, the CuO/Cu@PC composites achieved a remarkable 96.8 % degradation of ROX within 180 min, significantly outperforming unannealed samples (85.9 %). Furthermore, adsorption studies demonstrated a maximum ROX uptake capacity of 410 mg/g at optimal pH 5.5, following a pseudo-second-order kinetic model and Freundlich isotherm, suggesting a heterogeneous chemisorption process. The composite membranes exhibited outstanding long-term stability, maintaining over 85 % photocatalytic efficiency after 10 cycles. These results highlight the potential of CuO/Cu@PC membranes as highly effective and reusable materials for the sustainable removal of pharmaceutical contaminants, offering a scalable solution for water purification.